PEMANFAATAN BUKU TEKS OLEH GURU DALAM PEMBELAJARAN SEJARAH: STUDI KASUS DI SMA NEGERI KABUPATEN SEMARANG - Darwati, Darwati (Paramita: Historical Studies Journal, 2011)
Textbooks have an important meaning for teachers.ÃÂ Textbooks can serve as a source of learning and teaching history, because in it there is material, illustrations, and a variety of evaluation, so that learning objectives can be achieved in an optimal history.ÃÂ The first selection of textbooks criteria is based on the relevance of the material contained in a text book with the structure of the curriculum.ÃÂ The next criterion is completeness of the material, number of illustrations, and a diverse training and evaluation.ÃÂ In learning history, there are two types of utilization of textbooks, namely the use of textbooks that students already have the book and the use of textbooks to students who do not have.ÃÂ In the schools that their students have no textbooks, textbooks used in a way lent to students.ÃÂ Constraints in the use of textbooks are a relatively expensive price, there is no actually discourse of history, limited number of books, the library utilization is not optimal, and the limited use of information techno-logy of the Internet. These constraints are also factors that hinder the maximum use of textbooks. . ÃÂ  Key words: textbooks, teacher of history, learning history ÃÂ